Au-based catalyst for acceptor-free dehydrogenation reaction of biomass alcohol and preparation method of Au-based catalyst

By introducing reducing metals and inert metal cations on the surface of the LDHs support and loading Au nanoparticles, the problem of difficult overflow and binding of H species in the catalyst is solved, and the activity and stability of glycerol-free receptor dehydrogenation reaction is significantly improved.

CN119524873APending Publication Date: 2025-02-28BEIJING UNIV OF CHEM TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411717281.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing catalysts have the problem that H species are difficult to overflow and bind in the glycerol-free receptor dehydrogenation reaction, resulting in low activity and poor product selectivity.

Method used

By introducing reducing metals and inert metal cations on the surface of the layered composite metal hydroxide (LDHs) support and loading Au nanoparticles, a catalyst with atomic dispersion of Au-O-M1-O-M2/Al coordination structure is formed, and efficient overflow of H species is achieved by using electron-driven proton coupling transfer.

Benefits of technology

The activity of Au-based catalyst in glycerol-free receptor dehydrogenation reaction was significantly improved, the selectivity of H2 and the yield of lactic acid were improved, and the catalyst showed good stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005157147810000071
    Figure BDA0005157147810000071
  • Figure HDA0005157147820000011
    Figure HDA0005157147820000011
  • Figure HDA0005157147820000012
    Figure HDA0005157147820000012
Patent Text Reader

Abstract

The invention provides an Au-based catalyst for a receptor-free dehydrogenation reaction of biomass alcohol and a preparation method of the Au-based catalyst. The catalyst is expressed as Au / M1M2Al-LDO. Wherein M1 is a reducible metal cation, and M2 is a catalyst laminate skeleton inert element. The elements M1, M2 and Al are in atomic order dispersion in the catalyst, and form an Au-O-M1-O-M2 / Al coordination structure with Au; due to the non-reducibility of M2 metal, H species removed from the surface of the carrier cannot overflow through M2, the H species are promoted to efficiently overflow to an Au site only through M1 metal with reducibility, the collision probability of H is increased, and the H binding capacity is greatly improved. The catalyst is prepared by taking LDHs hydrotalcite with an ordered natural structure as a precursor, loading Au nanoparticles and then roasting at the temperature of 200-400 DEG C. According to the method disclosed by the invention, high-efficiency co-production of zero-carbon H2 and lactic acid in receptor-free dehydrogenation of glycerol by using the Au-based catalyst is realized, and the application field of the Au-based catalyst in upgrading and conversion of biomass resources is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of catalytic technology, and specifically relates to a method for co-producing zero-carbon H by receptor-free dehydrogenation of biomass platform molecule glycerol. 2 Catalyst and preparation technology of lactic acid Background Art

[0002] With the world's increasing reliance on non-renewable resources and the urgent need to transform into a low-carbon economy, hydrogen (H 2 ) has attracted much attention as a new type of high-energy chemical and ideal fuel. Traditional industrial hydrogen production is mainly based on steam methane reforming and coal gasification. However, this is a carbon-intensive process that poses considerable environmental challenges. The development of economical, green and sustainable hydrogen production technology is imminent. In this regard, renewable biomass acceptor-free dehydrogenation technology has attracted widespread attention. Glycerol, as a typical biomass platform molecule, can simultaneously produce H 2 and high-value lactic acid, achieving zero CO 2 Net emission of H 2 production, but also improve economic competitiveness.

[0003] In principle, the acceptor-free dehydrogenation of alcohols starts from the dissociation of C-OH and C-H bonds, where the removal of two H species occurs on the oxide support and the metal surface, respectively, and then the H species on the support surface overflow to the metal surface to generate H 2 and desorb (H*→H 2 ). Literature shows that noble metal Pt is usually used as an important component for CH bond activation in alcohol acceptor-free dehydrogenation reactions. Qi et al. 1 / CeO 2 Catalyst: a DRIFTS study, J.Am.Chem.Soc.; 2020, 143(1), 60-64, revealed the Pt / CeO 2 The metal-support synergistic dehydrogenation mechanism of the catalyst. Studies have shown that the O atom in -OH and CeO 2 The effective orbital overlap between the two can promote the rotation and dissociation of the -OH bond, while the interfacial interaction between the Pt-O-Ce coordination structure induces charge redistribution in Pt, prompting electron transfer from the catalyst interface to the alkoxide intermediate to complete the C α -H bond activation. However, Pt-based catalysts usually strongly adsorb products, resulting in easy deactivation of the catalyst. Therefore, the development of a new type of highly stable catalyst for receptor-free dehydrogenation of biomass alcohols is of great significance for the efficient utilization of biomass resources and the relief of energy pressure.

[0004] Au-based catalysts have excellent activation ability for C-H bonds and moderate adsorption ability for products, which can effectively avoid the above problems. However, since Au also has weak adsorption for H species, it is difficult for H species removed from the support surface to overflow to the Au site in time to combine into H 2 In the acceptor-free dehydrogenation reaction of glycerol, a higher reaction temperature is often required and the product selectivity is low. Palacio et al. 2 A series of Au-based catalysts were reported in J.Nanopart.Res., 2019, 21, e148 for catalytic acceptor-free dehydrogenation of glycerol. The results showed that the best AuCu / CeO 2 Under the reaction conditions of reaction temperature 250℃, catalyst input 600mg, and glycerol input 70mmol, the catalyst only obtained 87.2% glycerol conversion and 76.5% lactic acid selectivity. Solving the problem of H species difficulty in overflow binding in Au-based catalysts is expected to further improve the activity of glycerol receptor-free dehydrogenation.

[0005] Layered Double Hydroxides (LDHs) are a class of ionic layered compounds that consist of brucite-like layers with anions and H 2 O molecules. Some of the divalent metal cations with octahedral coordination of hydroxyl groups are replaced by trivalent metal cations. Due to the lattice energy minimization effect, M 2+ Ions are M 3+ The ions are highly dispersed, forming an atomically ordered M 2+ -OM 3+ Coordination structure. Utilizing the above characteristics, the present invention uses LDHs as a structural platform, introduces reducible metals and inert metal cations at the same time, and further loads Au nanoparticles with CH bond activation ability, and obtains Au-based catalysts with atomic-level dispersion between different metal cations on the carrier surface after calcination. Under the synergistic effect of reducible cations and inert metal cations on the carrier surface, the H species at the carrier are efficiently overflowed to the Au site through electron-driven proton coupling transfer, which greatly improves the activity of the Au-based catalyst in the receptor-free dehydrogenation reaction of alcohols. Summary of the invention

[0006] The purpose of the present invention is to provide an Au-based supported catalyst with hydrogen overflow function and a preparation method thereof. The catalyst is mainly used for the receptor-free co-production of zero-carbon H 2 and lactic acid.

[0007] The catalyst provided by the present invention is expressed as Au / M 1 M 2 Al-LDO, wherein Au is used as the CH bond activation site in the alcohol molecule, and the loading amount can be 0.05-5% by mass percentage. 1 M is a reducible metal cation, which can be any one of Ni, Fe, Co, Cu, Ga, and Ti, preferably Cu or Ni; 2 is an inert metal cation of the catalyst layer plate skeleton, which can be one of Mg, Ca, and Zn. In terms of molar percentage, M 1 / M 2 The ratio should be 1 to 6; (M 1 +M 2 ) / Al ratio should be 2-4.

[0008] The characteristics of this catalyst are:

[0009] The catalyst is Au / M 1 M 2 Al-LDHs is used as a precursor, and Au / M nanostructured nanostructures with dispersed metal atoms are obtained by calcining at a temperature below 400 °C. 1 M 2 Al-layered composite metal oxide (LDO). When calcined at a temperature below 400°C, M 1 M 2 In the Al-LDHs precursor, only some interlayer anions, H 2 O molecules and surface hydroxyl groups are removed, while the natural ordered metal cation arrangement and structure are retained, and Au-OM is formed with Au. 1 -OM 2 / Al coordination structure. According to the characteristics of the alcohol's receptor-free dehydrogenation reaction, the C-OH and CH bonds of the alcohol molecule are activated at the O atom and Au site on the support surface, respectively. 2 The irreducibility of the metal results in the obstruction of the overflow of H species removed from the support surface in this direction, thus 1 The metal efficiently overflows to the Au site, greatly improving the H species binding ability.

[0010] The specific preparation steps of the catalyst provided by the present invention are as follows:

[0011] A. M 1 Salt, M 2Salt and Al salt are mixed and dissolved in ultrapure water, and ultrasonically dissolved to obtain solution A. The amount of salt added is based on the M to be prepared. 1 M 2 Al-LDHs quantification, the total concentration of the three metal cations is 0.3-1.2 mol / L, and the metal salt ion can be NO 3- , Cl - 、SO 4 2- One or more of the .

[0012] B. Dissolve the alkali in ultrapure water of equal volume to solution A, and dissolve it evenly by ultrasound to obtain solution B; the alkali can be NaOH, KOH, Na 2 CO 3 and CO(NH 2 ) 2 One or more of the above; wherein the total concentration of the alkali is 0.6 to 3.6 mol / L; at the same time, according to the charge balance principle between the hydrotalcite layers and the layers, the charge number of the anions in the alkaline solution should be 1 to 2 times the charge number of the cations in solution A.

[0013] C. Slowly add solution A and solution B to the three-necked flask with a magnetic element through a constant pressure burette, and set the rotation speed to 600 rpm. During the titration process, the pH of the mixed solution is maintained between 9 and 10; the mixed solution is crystallized at a temperature of 60 to 120°C for 6 to 12 hours, and the supernatant is washed by centrifugation until it is neutral, and then placed in a vacuum drying oven for drying to obtain series M 1 M 2 Al-LDHs precursor A.

[0014] D. Take M 1 M 2 Al-LDHs precursor A was evenly dispersed in ultrapure water, and the required amount of HAuCl was added dropwise 4 ·3H 2 O solution with a concentration of 10-50 mmol / L. Stir at 60°C and 600 rpm for 2 hours. Then place the solution in an ice-water bath and add freshly prepared NaBH 4 Solution is used to reduce the loaded Au 3+ ions, including NaBH 4 With the addition of Au 3+ The molar ratio of ions was 5:1, and stirring was continued for 1 hour. Washing and freeze-drying were performed to obtain a series of Au / M 1 M 2 Al-LDHs precursor B.

[0015] E. Take Au / M 1 M 2The Al-LDHs precursor B is ground evenly and then calcined in a muffle furnace. The calcination conditions are: heating to 200-400°C at a rate of 2-10°C / min, keeping for 3-6 hours and then taking out at room temperature to obtain a series of Au / M 1 M 2 The Al-LDO catalyst was stored in vacuum for future use.

[0016] Figure 1 The high-resolution transmission electron microscope (HRTEM) photos and particle size distribution diagrams of the catalysts prepared in Examples 1 and 2 show that the active metal Au is uniformly dispersed on the surface of the carrier in the form of nanoparticles with a size range of 3 to 4 nm.

[0017] Figure 2 The X-ray diffraction (XRD) spectra of the catalysts prepared in Examples 1 and 2 show that a series of well-developed reflection peaks related to the typical LDHs phase can be clearly observed in the prepared precursors. At the same time, after low-temperature calcination, the characteristic diffraction peaks (110) and (113) of the layered structure are well preserved, indicating that M 1 M 2 The Al-LDO carrier inherits the orderly arrangement of atoms in the LDHs precursor.

[0018] Figure 3 The mass spectra (MS) of the catalysts prepared in Application Example 1 and Comparative Example 1 in the glycerol acceptor-free dehydrogenation reaction show that the gas phase components of the reaction system in Application Example 1 are only N 2 and H 2 , no CO was detected 2 In Comparative Example 1, N 2 And a small amount of H 2 , and there is CO 2 Generation of.

[0019] Figure 4 The results of repeated stability experiments of the catalyst prepared in Application Example 1 in the acceptor-free dehydrogenation reaction of glycerol show that the catalyst was recycled eight times without showing any obvious deactivation, indicating excellent stability.

[0020] The beneficial effects of the present invention are:

[0021] Based on the natural ordered and highly dispersed structural characteristics of LDHs, reducible metals and inert metal cations were introduced to further load Au nanoparticles with CH bond activation ability, and Au-OM with ordered atomic arrangement was obtained by low temperature calcination. 1 -OM 2Au-based catalysts with Au / Al coordination structures. Such catalysts can be used in the receptor-free dehydrogenation of glycerol to promote the efficient overflow of H species removed from the support surface to the Au sites, increase the collision probability of H, and thus greatly improve the activity of receptor-free dehydrogenation. At the same time, the catalysts show good stability and have broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 High resolution transmission electron microscopy (HRTEM) images of the catalysts prepared in Examples 1 and 2.

[0023] Figure 2 The X-ray diffraction (XRD) diagram of the catalyst prepared in Examples 1-2.

[0024] Figure 3 This is the mass spectrum (MS) of the catalyst prepared in Application Example 1 in the acceptor-free dehydrogenation reaction of glycerol.

[0025] Figure 4 These are the results of repeated stability experiments of the catalyst prepared in Application Example 1 in the acceptor-free dehydrogenation reaction of glycerol. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with the embodiments, but it does not constitute a limitation on the protection scope of the present invention.

[0027] Example 1

[0028] A. Accurately weigh 0.0072 mol Cu(NO 3 ) 2 6H 2 O, 0.036 mol Mg(NO 3 ) 2 6H 2 O and 0.0216 molAl(NO 3 ) 3 9H 2 O, and ultrasonically dissolve it uniformly in ultrapure water to obtain solution A.

[0029] B. Accurately weigh 0.1 mol NaOH and 0.05 mol Na 2 CO 3 , ultrasonically dissolve evenly in ultrapure water to obtain solution B.

[0030] C. Add solutions A and B to a three-necked flask through a constant pressure burette and set the speed to 600 rpm. Maintain the pH of the mixed solution at 9 by adjusting the dropping speed of solution B, and add until solution A is consumed. Crystallize at 80°C for 8 hours, centrifuge and wash the supernatant to neutrality, then put it into a vacuum drying oven for drying to obtain the precursor CuMgAl-LDHs.

[0031] D. Take 0.5g of CuMgAl-LDHs precursor and disperse it evenly in ultrapure water by ultrasonication, then add 1.35ml of HAuCl with a concentration of 22.38mmol / L dropwise. 4 ·3H 2 O solution. Stir at 60°C for 2 hours. Then place the solution in an ice-water bath and add 10 ml of freshly prepared NaBH 4 The solution (concentration 15 mmol / L) was stirred for 1 hour, washed by centrifugation until neutral, and freeze-dried to obtain the precursor Au / CuMgAl-LDHs.

[0032] E. Grind the precursor evenly and then calcine it in a muffle furnace. The calcination conditions are as follows: heat up to 300°C at a heating rate of 10°C / min, keep it for 3 hours, then cool it down to room temperature and take it out to obtain Au / CuMgAl-LDO catalyst, which is vacuum sealed and stored for later use.

[0033] Application Example 1

[0034] 30 mg of the above catalyst was placed in a stainless steel reactor, and then 15 mmol of glycerol was added as the reaction solution. An inert atmosphere of N 2 The air in the reactor was replaced and the pressure in the reactor was maintained at 1.0 MPa. The temperature in the reactor was maintained at 180°C and the speed was set to 800 rpm by magnetic stirring for reaction. After 2 hours of reaction, the liquid phase product and the gas phase product were collected through the liquid phase valve and the gas phase valve, respectively, and analyzed and tested. The results are shown in Table 1.

[0035] The catalyst was used repeatedly for 8 times to determine its reusability. After each reaction, the catalyst was recovered and washed with deionized water, dried and put into the next cycle. The results are shown in Table 2. Figure 4 .

[0036] Example 2

[0037] A. Accurately weigh 0.0036 mol NiCl 2 6H 2 O, 0.072 mol CaCl 2 ·2H 2 O and 0.0422 molAlCl 3 6H 2 O, and ultrasonically dissolve it uniformly in ultrapure water to obtain solution A.

[0038] B. Accurately weigh 0.05 mol KOH and 0.15 mol Na 2 CO 3 , ultrasonically dissolve evenly in ultrapure water to obtain solution B.

[0039] C. Add solutions A and B to a three-necked flask through a constant pressure burette, and set the speed to 600 rpm. Maintain the pH of the mixed solution at 9 by adjusting the dropping speed of solution B, and add until solution A is consumed. Crystallize at 100°C for 6 hours, centrifuge and wash the supernatant to neutrality, and then put it into a vacuum drying oven for drying to obtain the precursor NiMgAl-LDHs.

[0040] D. Take 0.5g of NiMgAl-LDHs precursor and disperse it evenly in ultrapure water by ultrasonication, then add 2.7ml of HAuCl with a concentration of 22.38mmol / L dropwise. 4 ·3H 2 O solution. Stir at 60°C for 2 hours. Then place the solution in an ice-water bath and add 10 ml of freshly prepared NaBH 4 The solution (concentration is 30mmol / L) was stirred for 1 hour, washed by centrifugation until neutral, and freeze-dried to obtain the precursor Au / NiMgAl-LDHs.

[0041] E. Grind the precursor evenly and then calcine it in a muffle furnace. The calcination conditions are as follows: heat up to 300°C at a heating rate of 5°C / min, keep it for 3 hours, then cool it down to room temperature and take it out to obtain Au / NiMgAl-LDO catalyst, which is vacuum sealed and stored for later use.

[0042] Application Example 2

[0043] 30 mg of the above catalyst was placed in a stainless steel reactor, and then 15 mmol of glycerol was added as the reaction solution. An inert atmosphere of N 2 The air in the reactor was replaced and the pressure in the reactor was maintained at 0.5 MPa. The temperature in the reactor was maintained at 140°C and the reaction was carried out at a speed of 800 rpm by magnetic stirring. After 3 hours of reaction, the liquid phase product and the gas phase product were collected through the liquid phase valve and the gas phase valve, respectively, and analyzed and tested. The results are shown in Table 1.

[0044] Example 3

[0045] A. Accurately weigh 0.0144 mol CoCl 2 6H 2 O, 0.072 mol CaCl 2 ·2H 2 O and 0.0378 mol Al(NO 3 )3 9H 2 O, and ultrasonically dissolve it uniformly in ultrapure water to obtain solution A.

[0046] B. Accurately weigh 0.3 mol KOH and dissolve it evenly in ultrapure water by ultrasonication to obtain solution B.

[0047] C. Add solutions A and B to a three-necked flask through a constant pressure burette and set the speed to 600 rpm. Maintain the pH of the mixed solution at 9 by adjusting the dropping speed of solution B, and add until solution A is consumed. Crystallize at 60°C for 10 hours, centrifuge and wash the supernatant to neutrality, then put it into a vacuum drying oven for drying to obtain the precursor CoMgAl-LDHs.

[0048] D. Take 0.5g of CoMgAl-LDHs precursor and disperse it evenly in ultrapure water by ultrasonication, then add 2.7ml of HAuCl with a concentration of 22.38mmol / L dropwise. 4 ·3H 2 O solution. Stir at 60°C for 2 hours. Then place the solution in an ice-water bath and add 10 ml of freshly prepared NaBH 4 The solution (concentration is 30 mmol / L) was stirred for 1 hour, washed by centrifugation until neutral, and freeze-dried to obtain the precursor Au / CoMgAl-LDHs.

[0049] E. Grind the precursor evenly and then calcine it in a muffle furnace. The calcination conditions are as follows: heat up to 400°C at a heating rate of 2°C / min, keep it for 3 hours, then cool it down to room temperature and take it out to obtain Au / CoMgAl-LDO catalyst, which is vacuum sealed and stored for later use.

[0050] Application Example 3

[0051] 30 mg of the above catalyst was placed in a stainless steel reactor, and then 15 mmol of glycerol was added as the reaction solution. An inert atmosphere of N 2 The air in the reactor was replaced and the pressure in the reactor was maintained at 1.0 MPa. The temperature in the reactor was maintained at 160°C and the reaction was carried out at a speed of 800 rpm by magnetic stirring. After 2 hours of reaction, the liquid phase product and the gas phase product were collected through the liquid phase valve and the gas phase valve, respectively, and analyzed and tested. The results are shown in Table 1.

[0052] Comparative Example 1

[0053] Accurately weigh the purchased commercial Al 2 O 3 0.5 g of the carrier was evenly dispersed in ultrapure water by ultrasonication, and 2.7 ml of HAuCl with a concentration of 22.38 mmol / L was added dropwise. 4 ·3H 2O solution. Stir at 60°C for 2 hours. Then place the solution in an ice-water bath and add 10 ml of freshly prepared NaBH 4 The solution (concentration is 30mmol / L) was stirred for 1 hour, centrifuged and washed until neutral, and freeze-dried to obtain the catalyst Au / Al 2 O 3 .

[0054] Referring to the reaction conditions of Application Example 1, the catalyst Au / Al 2 O 3 The acceptor-free dehydrogenation performance was evaluated and the results are shown in Table 1.

[0055] Table 1 Series Au / M 1 M 2 Acceptor-free Dehydrogenation Activity of Glycerol over Al-LDO Catalyst

[0056]

[0057] As can be seen from Table 1, the catalyst prepared by the present invention has good activity in the process of acceptor-free co-production of hydrogen and lactic acid from biomass alcohol-glycerol. Taking Application Example 1 as an example, through the present invention, after reacting at a temperature of 180° C. for 2 hours, the conversion rate of glycerol is 99.3%, and the selectivity of lactic acid and hydrogen is as high as 98.8% and 99.7%, respectively, which is much higher than that of Comparative Example 1, indicating its excellent dehydrogenation activity.

[0058] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. An Au-based catalyst for acceptor-free dehydrogenation of biomass alcohols, characterized in that: It is expressed as Au / M1M2Al-LDO, where LDO is a layered composite metal oxide; Au serves as the CH bond activation site in the alcohol molecule, and the loading amount is 0.05-5% by mass percentage; M1 is a reducible metal cation, and M2 is an inert metal cation in the catalyst layer plate skeleton, wherein the ratio of M1 / M2 should be 1-6 by mole percentage; and the ratio of (M1+M2) / Al should be 2-4.

2. The catalyst according to claim 1, characterized in that: M1 is any one of Ni, Fe, Co, Cu, Ga, and Ti.

3. The catalyst according to claim 2, characterized in that: M1 is Cu or Ni.

4. The catalyst according to claim 1, characterized in that: M2 is one of Mg, Ca and Zn.

5. The catalyst according to claim 1, characterized in that: The catalyst uses Au / M1M2Al-LDHs as a precursor, and is calcined at a temperature below 400°C to obtain Au / M1M2Al-layered composite metal oxide with carrier metal atoms dispersed therein.

6. A method for preparing the catalyst according to claim 1, characterized in that: The specific preparation steps are as follows: A. M1 salt, M2 salt and Al salt are mixed and dissolved in ultrapure water, and ultrasonically dissolved to obtain solution A. The amount of salt added is quantitatively determined according to the M1M2Al-LDHs to be prepared. The total concentration of the three metal cations is 0.3-1.2 mol / L. The metal salt ion is NO 3- , Cl - 、SO4 2- One or more of the following; B. dissolving the alkali in ultrapure water of equal volume to that of solution A, and dissolving it uniformly by ultrasonication to obtain solution B; the alkali may be one or more of NaOH, KOH, Na2CO3 and CO(NH2)2; wherein the total concentration of the alkali is 0.6-3.6 mol / L; the charge number of the anions in the alkali solution should be 1-2 times the charge number of the cations in solution A; C. Add solution A and solution B to a three-necked flask with a magnet through a constant pressure burette, and set the rotation speed to 600 rpm; maintain the pH of the mixed solution between 9 and 10 during the titration process; crystallize the mixed solution at a temperature of 60 to 120°C for 6 to 12 hours, centrifuge and wash the supernatant to neutrality, and then put it into a vacuum drying oven for drying to obtain a series of M1M2Al-LDHs precursor A; D. Take M1M2Al-LDHs precursor A and disperse it evenly in ultrapure water, add the required amount of HAuCl4·3H2O solution drop by drop, the solution concentration is 10-50mmol / L; stir at 60℃ and 600rpm for 2 hours; then place the above solution in an ice water bath, and add freshly prepared NaBH4 solution drop by drop to reduce the loaded Au 3+ ions, where NaBH4 and the added Au 3+ The molar ratio of ions was 5:1, and stirring was continued for 1 hour; washing and freeze-drying were performed to obtain a series of Au / M1M2Al-LDHs precursors B; E. Grind Au / M1M2Al-LDHs precursor B evenly, and then calcine it in a muffle furnace; the calcination conditions are: heating the temperature to 200-400°C at a heating rate of 2-10°C / min, keeping it at room temperature for 3-6 hours, and then taking it out to obtain a series of Au / M1M2Al-LDO catalysts, which are stored in a vacuum for future use.